أثر تبني معايير ادارة الجودة الشاملة على تسويق الخدمات الصحية - بقاط, حسين; مديني, عثمان; جرمون, محمد الطاهر (University of eloued جامعة الوادي, 2018)
The aim of thisstudyis to understand the impact of TQM on the marketing of health services in a sample of healthorganizations (Al-NourHospital in Tunis, Al-RimalHospital in Al-OUED, General Hospital of Ben-Omar El-Gilani in Al- OUED, Marketing of health services from the viewpoint of the provider and the recipient, in addition to identifying the gaps between the healthorganizations on evaluating the marketing of health services from the viewpoint of the provider and the recipient In order to achieve the objectives of thisstudy, werelied on the descriptive approach to suit the problem of the study and the use of the questionnaire as a tool for collecting data in the fieldstudythroughtwo questionnaires addressed to the service providers containing 44 questions, the second addressed to the recipients of the service and 31 questions, A valid application form for the service provider and 100 validforms for the recipient. After the statisticalprocessing and testinghypotheses, wereachedseveralresults, the most important of which are: - The recipient of the service considersthatachieving a good level of marketing of health services ismanifestedthrough attention to service, processes, individuals and physicalevidence as the basis for the provision of good services; - The results of the studyshowedthatthere are gaps in the level of provision of health service in the clinicsstudiedbetween the views of the provider and the recipient in theirassessment of the levels of someelements of the marketing mix, whiletheyshowed a match in eachother; - The results of the studyshowedthat the adoption of TQM as an administrative philosophy has a positive impact on the marketing of the health service. - The results of the studyshowedthat the criterion of "employee participation" in adopting the top management of the philosophy of TQM has the most important effect on the positive impact on the marketing of health services at the level of the studiedorganizations
مذكرة ماستر ادارة اعمال
Keywords: ادارة الجودة الشاملة ، تسويق الخدمات الصحية